Tablets for image review and communication in daily routine of orthopedic surgeons: an evaluation study - Vetter, Sven Y.; Schüler, Svenja; Hackbusch, Matthes; Müller, Michael; Swartman, Benedict; Schnetzke, Marc; Grützner, Paul Alfred; Franke, Jochen (Journal of digital imaging, 2018)
Medical images are essential in modern traumatology and orthopedic surgery. Access to images is often cumbersome due to a limited number of workstations. Moreover, due to the tremendous increase of data, the time to review or to communicate images has also become limited. One approach to overcome these problems is to make use of modern mobile devices, like tablet computers, to facilitate image access and associated workflows. Ten orthopedic surgeons were equipped with an Apple iPad mini 2 and specialized viewing software for medical images. The surgeons were able to send images from a workstation onto the tablets or to search for patient images directly. The software enabled the physicians to share images, annotated key slices, and messages instantly with their colleagues. The surgeons carried the tablets within or in the periphery of the hospital. The participants evaluated the software by means of daily questionnaires. Data was collected for a period of 9 months. Nearly 25 images were viewed in total by the surgeons per day. The tablet viewer was used for accessing approximately 30% of these images. On average, the surgeons were asked 1.7 times per day by a colleague for a second opinion. They used the tablets in approximately 29% of these cases. Furthermore, the mean time for accessing images was significantly lower using mobile software compared to conventional methods. Tablet computers can play a vital role for image access and communication in the daily routine of an orthopedic surgeon. Mobile image access is an important aspect for surgeons, especially in larger facilities, to facilitate and accelerate the clinical workflows.
Published online: 10 August 2017
Gesehen am 15.04.2020